Occupational stress and social support among nurses - Dziedzic, Beata; Łodziana, Karolina; Marcysiak, Miłosz; Kryczka, Tomasz (Frontiers in Public Health, 2025)
IntroductionNursing is a profession that involves a significant emotional, physical, and intellectual load. Nurses frequently encounter various stressors, not only due to the nature of their responsibilities but also resulting from organizational factors and interpersonal relationships in the workplace. In this context, social support plays a crucial role in helping individuals cope with stress. It may serve as a protective buffer, promoting positive emotional outcomes and reducing the level of perceived stress. The aim of this study was to analyze stress levels and perceived social support among actively working nurses and to assess the relationship between these two variables.MethodsThe survey included 321 nurses employed at medical facilities. Data collection took place between November 2022 and February 2023. The study was based on a Polish-language survey questionnaire developed through Google Forms, which was distributed via nursing association websites to reach the target audience. Stress levels were measured using the Perceived Stress at Work (PSWP) Questionnaire. Support level was assessed using the Multidimensional Scale of Perceived Social Support (MSPSS).ResultsThe average stress level on the PSWP scale was 18.45 ± 5.89, while the average general support score on the MSPSS scale was 63.18 ± 14.78, with the highest support reported from family (21.35 ± 5.3). Analyses revealed a statistically significant negative correlation between MSPSS and PSWP scores (r = −0.21; p = 0.002).ConclusionThe findings of this study suggest that most nurses experience moderate levels of perceived stress alongside relatively high levels of social support. Notably, both stress and social support were significantly associated with nurses’ age and workplace setting, indicating that demographic and organizational factors may influence their psychological well-being. These results underscore the need for targeted interventions to reduce stress and strengthen support systems, particularly for younger nurses and those working in high-intensity clinical settings. Further research is warranted to examine causal relationships and to inform the development of tailored support programs within healthcare institutions.